Sex determination in Drosophila: sis-b, a major numerator element of the X:A ratio in the soma, does not contribute to the X:A ratio in the germ line. - Steinmann-Zwicky, M. (Development, 1993)
In soma and germ cells of Drosophila, the X:A ratio builds a primary signal for sex determination, and in both tissues Sex-lethal (Sxl) function is required for cells to enter the female pathway. In somatic cells of XX animals, the products of X-chromosomal elements of the X:A ratio activate Sxl. Here I show that sisterless-b (sis-b), which is the X-chromosomal element of the somatic X:A ratio that has best been analysed, is not required for oogenesis. I also present evidence that Sxl function might not be sufficient to direct germ cells into the female pathway. These results show that the elements forming the X:A ratio in the germ line are different from the elements forming the X:A ratio in the soma and they suggest that, in the germ line, Sxl might not be regulated by the X:A ratio.